Sauropus androgynus (L.) Merrill-A Potentially Nutritive Functional Leafy-Vegetable - Petrus, A.J.A. (Asian Journal of Chemistry, 2013)
Sauropus androgynus (L.) Merrill [Family: Phyllanthaceae Martynov] is a popular leafy-vegetable in South and Southeast Asia and is notable for its high yields and palatability. The leaves and succulent young tips of the plant are normally eaten like tropical asparagus, raw in the form of salads or steamed or alternatively added to stir-fry, rice and egg dishes, soups or casseroles, and sometimes blanched to serve with chilli paste. The rich vitamin content of the leaves has led to its popular name, ‘multivitamin green’ and has also been recorded as a tropical vegetable by the United States Department of Agriculture. The flowers and the small purplish fruits of the plant are also reported to be eaten. The present paper attempts to review the health-impact of the nutritive factors and other phytometabolites biosynthesized by this functional leafy-vegetable, in addition to its ethnomedical claims.